Strategi Kesantunan dalam Dakwah: Studi pada Ceramah Gus Iqdam di YouTube - Ibrahim, Azzam Zafir; Anam, Moh Khoirul (Journal of Islamic Communication Studies, 2026)
The dynamics of da‘wah in the digital era are frequently confronted with the challenge of maintaining ethical communication within fluid public spheres. This academic concern arises from the phenomenon of da‘wah content that often appears confrontational and insufficiently sensitive to the audience’s “face,” thereby potentially diminishing the effectiveness of message delivery. This study aims to analyze the politeness strategies employed in the preaching communication of Gus Iqdam.  Adopting a qualitative research design, the study examines three sermon transcripts from Gus Iqdam’s official YouTube channel. Data analysis is conducted using the Politeness Theory framework developed by Penelope Brown and Stephen C. Levinson. The findings reveal that Gus Iqdam predominantly employs positive politeness strategies, manifested through intimate forms of address, humor, and personal storytelling to foster closeness and solidarity with the audience. Complementarily, he applies negative politeness strategies, such as the use of refined language and apologies to respect the personal space of congregants, as well as off-record strategies through analogies and rhetorical questions to convey criticism indirectly. This combination of strategies successfully generates an inclusive, effective, and minimally face-threatening model of da‘wah communication. The study concludes by proposing a contextualized politeness strategy model for digital preachers-one that not only aims to disseminate religious messages but also to cultivate positive and sustainable relationships with audiences in digital environments.